Corporate Social Responsibility and Financial Performance: The Case of ASEAN Telecommunications Companies - Hashim, Fathyah; Ahmad Ries, Essia; Teck Huai, Ng (KnE Social Sciences, 2019)
This paper examines the relationship between corporate social responsibility and financial performance in ASEAN (The Association of Southeast Asian Nations (ASEAN) is a regional intergovernmental organization comprising ten countries in Southeast Asia, which promotes intergovernmental cooperation and facilitates economic, political, security, military, educational, and sociocultural integration among its members and other countries in Asia) telecommunications companies. Corporate social responsibility (CSR) dimensions assessed in this study include community, corporate governance, employee relations, and the environment. Meanwhile, financial performance is obtained by analysing the organisation’s return on assets (ROA). Although there have been past studies, investigate the relationship between CSR and Financial Performance (FP), cross-country, and through structural equation modeling, there is still a lack of data focusing in ASEAN telecommunications industry. Therefore, using 17 telecommunications companies in ASEAN countries based on their five years’ annual reports (2013-2017), this study attempt to provide empirical evidence on the possible relationship between CSR and FP. However, this study found no significant relationship between the two. This study provides a more in-depth understanding theoretically and practically on corporate social responsibility on financial performance in ASEAN telecommunications industry.